Efeito do Tratamento com Hidróxido de Sódio sobre a Fração Fibrosa, Digestibilidade e Tanino do Feno de Jurema-Preta (Mimosa tenuiflora. Wild) - Pereira Filho, José Morais [UNESP]; De Lucena Vieira, Ednéia; De Azevedo Silva, Aderbal Marcos; Cezar, Marcílio Fontes; Amorim, Francisco Uchoa (FapUNIFESP (SciELO), 2003)
The experiment was carried out to evaluate the effect of sodium hydroxide (NaOH) on fiber fraction, tannin level and dry matter in vitro digestibility of jurema-preta hay. Leaves were harvested by hand and dried under shadow. Chemical treatment consisted of hay pulverization with 0; 2; 4; 6 and 8% NaOH solution, following the proportion of 1 liter of solution to 1 kg of hay. Samples of hay were submitted to determination of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), tannin and DM in vitro digestibility which were the evaluated variable. A completely randomized design with five treatments and four replicates was used. NaOH treatment showed linear effect for DM, hemicellulose and tannin contents, while for NDF and ADF was observed quadratic effect. CP was not affected and DMIVD was improved by NaOH concentration increase. DMIVD estimated by tannin content need to be more studied, instead of its significance.
Effect of Sodium Hydroxide Treatment on Fiber Fraction, Digestibility and Tannin of Jurema-Preta Hay (Mimosa tenuiflora. Wild)
Keywords: Acid detergent fiber; Legume; NaOH; Neutral detergent fiber; Mimosa; Mimosa tenuiflora